Some Essentials of Data Analysis with Wavelets : Lecture notes in the wavelet part of the course in data analysis at The Swedish National Graduate School of Space Technology, Kiruna and Luleå, November–December 2009 - Grip, Niklas (Luleå tekniska universitet, Matematiska vetenskaper, 2009)
Godkänd; 2009; 20101112 (grip)